Pengaruh Sektor Pariwisata Terhadap Tingkat Kemiskinan di Provinsi Nusa Tenggara Timur Tahun 2022 dengan Pendekatan Analisis Spasial - Taufiqqurrahman, M.; Marsisno, Waris (Politeknik Statistika STIS, 2024)
Poverty remains one of the serious issues in East Nusa Tenggara Province. In 2022, the province ranked third highest in poverty rates in Indonesia. One strategy to alleviate poverty is through tourism. This research aims to identify variables from the tourism sector influencing the poverty rate in East Nusa Tenggara Province in 2022, considering spatial effects. The research results indicate a positive spatial dependency on the poverty rate. By applying the Spatial Autoregressive Model (SAR), it was found that the variables number of domestic and foreign tourist, the number of restaurants, and the percapita GDP of tourism have a negative and significant impact on the poverty rate. Meanwhile, the variable number of accommodation does not significantly affect the poverty rate. Additionally, a simple dashboard has been created to display the actual poverty mapping and the results of spatial model estimation of poverty rates in East Nusa Tenggara Province in 2022.